Dendrobium huoshanense C. Z. Tang and S. J. Cheng can be prepared as a food with the ability to prevent and treat hyperuricaemia - Hao, Qing; Jiang, Lin; Ma, Jun; Wang, Huikai; Liu, Ying; Xu, Qichang; Li, Songze; Han, Song; Zheng, Qiusheng; Fan, Xiangcheng; Han, Jichun (Frontiers in Nutrition, 2025)
BackgroundHyperuricemia (HUA) is the presence of excessive uric acid (UA) in blood, which leads to an increased risk of chronic kidney disease and gout. There are about 120 million hyperuricemia patients in China, which has surpassed diabetes as the second largest chronic disease.ObjectiveThe aim of the present study was to investigate the hypouricemic effects of Dendrobium huoshanense C. Z. Tang and S. J. Cheng (DH), and provide a basis for its development into anti HUA products.MethodsThis study established a mouse HUA model by gavage of potassium oxonate (PIO) and hypoxanthine (HX), and treated with DH to investigate the therapeutic effect of DH on hyperuricemia. Use a biochemical assay kit to detect changes in the levels of UA, creatinine (Cr), and urea nitrogen (BUN) in mouse serum; Use ELISA kit to detect the activity of xanthine oxidase (XOD) in serum; Untargeted Metabolomics analysis was performed on the serum of each group of mice using liquid chromatography-mass spectrometry. This study recruited 23 HUA volunteers, volunteers drank 0.5 g DH daily for four consecutive weeks, with serum UA levels measured once a week.ResultsAnimal experiments have shown that DH has therapeutic effects on HUA, mainly manifested as: DH effectively reduces the levels of UA, Cr, and BUN in the serum of HUA mice, lowers XOD activity in the serum, and alleviates kidney tissue and glomerular damage. Metabolomics analysis showed that there were 306 significant differences in metabolites between the Sham group, HUA model group, and DH group. Pathway analysis of these differential metabolites revealed that they were mainly involved in pyrimidine metabolism, histidine metabolism, and riboflavin metabolism. Clinical research results show that after drinking DH, UA levels in HUA volunteers significantly decreased, and most HUA volunteers' UA levels decreased to normal levels.ConclusionDH has the effect of preventing and treating hyperuricemia, and it belongs to the same class of traditional Chinese medicine as medicine and food, with extremely low toxicity and high safety. Therefore, DH is suitable for preparation as a product for preventing and treating HUA in functional food and other products.